Sacralizing violence in Byzantium - Demacopoulos, George E. (Washington, DC)
viii, 244 sayfa
Keywords: “Christians had always been concerned, since the faith's inception, about the relationship between violence and belief. In Byzantium, this tension was explored not only in abstract theological texts but in the songs people sung: hymns, a multivalent, fluid form of devotion that served as the meeting place between theological conviction and lived religious experience. Sacralizing Violence in Byzantium is the first book to examine the complex and shifting perceptions of premodern Christians toward violence and war through the lens of hymnography. This book argues that the liturgical reflection on violence in Byzantium underwent a profound transformation-a sacralization of violence-at approximately the same time that Persian and then Arab armies conquered Jerusalem in the early seventh century, a turn that persisted into the tenth century. By focusing on hymnography, this book provides both correction and nuance to historical assessments of Eastern Christian attitudes toward war and violence and reveals how Byzantine culture dramatized, authorized, and even celebrated violence“ --